Study of Experimental Vaccination in White Pekin Duck (Anas platyrhynchos) Against Newcastle Disease: Investigation of the State of Virus Carrier - Nishizawa, Marcia; Paulillo, Antonio Carlos; Alessi, Antonio Carlos; Nunes, Aryana Duker; Campioni, Josie Maria; Nakaghi, Laura Satiko Okada; Junior, Luciano Doretto; Lima, Fabiana Silva (International Journal of Poultry Science, 2006)
This study aimed the characterization of the importance of vaccination against Newcastle disease in white Pekin duck (Anas platyrhynchos), and investigated the state of carrier of the virus in this species. There were used 120 Pekin ducks, distributed at random into 4 groups, vaccinated or not. At 60 days of age, all groups were challenged with a pathogenic virus (NDV) suspension, EID50 = 108,15/0,1mL. Cloacal and tracheal swabs were collected after 6, 14, 20 and 30 days post-challenge for viral isolation in SPF embryonated eggs. White Pekin duck of all the groups did not demonstrate symptoms of the Newcastle disease. They were refractory to the clinical disease with the NDV. In Pekin ducks from control group, the viral isolation was obtained from 20 up to 30 days after challenge. It was demonstrated therefore the state of carrier of NDV of the Pekin duck. In ducks from vaccinated groups, the viral isolation was null. It was also demonstrated therefore the importance of the vaccination in the suppression of the state of carrier of the NDV in white Pekin ducks.